“Haram, she’s obese!” Young Lebanese-Canadian Women’s Discursive Constructions of “Obesity” - Abou-Rizk, Zeina; Rail, Geneviève (Atlantis, 2015)
Using feminist poststructuralist and postcolonial lenses, we explore how young Lebanese-Canadian women construct “obesity” within the context of the current and dramatic hype about “obesity” and its impacts on the health of individuals and populations. Participant-centered conversations were held with twenty young Lebanese-Canadian women between the ages of eighteen and twenty-five. In examining what discourses the participants adopted, negotiated, and/or resisted when discussing “obesity,” we found that the young women constructed it as a problematic health issue and a disease, as a matter of lack of discipline, and as an “abnormal” physical attribute. They also expressed feelings of disgust and/or pity toward “obese” women by using the Arabic term “haram” (what a shame or poor her). While the participants emphasized that Lebanese and Lebanese-Canadian cultures prize physical appearance and “not being fat,” they also attempted to dissociate themselves from “Lebanese” ways of thinking and, in doing so, reproduced a number of stereotypes about Lebanese, Lebanese-Canadian, and Canadian women.